The influence of the morphological characteristics of nanoporous anodic aluminium oxide (AAO) structures on capacitive touch sensor performance: a biological application. Issue 65 (6th November 2018) - Carneiro, J. O.; Machado, F.; Pereira, M.; Teixeira, V.; Costa, M. F.; Ribeiro, Artur; Cavaco-Paulo, Artur; Samantilleke, A. P.
Abstract : This work is devoted to the study of the influence of different anodic aluminium oxide (AAO) morphologies on the sensitivity and performance of an AAO-based capacitive touch sensor. Abstract : This work is devoted to the study of the influence of different anodic aluminium oxide (AAO) morphologies on the sensitivity and performance of an AAO-based capacitive touch sensor. The AAO structures were fabricated in a cylindrical homemade anodization cell made from a solid polycarbonate billet via a lathe machining process. The AAO morphologies were obtained from the anodization of Al foil by using three different types of electrolyte (sulphuric acid, oxalic acid and phosphoric acid) and their morphologies are reported and compared using scanning electron microscopy (SEM) micrographs and current–time characteristic curves. The sensors were fabricated by integrating the AAO structure with a nanotextured gold thin film deposited over the AAO layer by thermal evaporation, thus realizing a type of metal/insulator/metal parallel-plate capacitance sensor. It is demonstrated that AAO morphologies have influence on the performance of the AAO-based capacitive touch sensors. The variation of the capacitance of the sensors is investigated in this work for the AAO structures produced from anodization in an attempt to select anodizing conditions for a biological application aiming to detect small microorganisms such as bacterial colonies of Escherichia coli .